Respostas
respondido por:
0
respondido por:
0
a³ + b³ = 16 e a²b + ab² = 8, (a + b)³ = ?
(a + b)³ = (a + b).(a + b).(a + b)
= (a + b)². (a + b)
= ( a² + 2ab + b²) . (a + b)
= a³ + 2a²b + ab² + a²b + 2ab² + b³
= a³ + b³ + 3.a²b + 3.ab²
= a³ + b³ + 3.(a²b + ab²) (substituindo)
= 16 + 3 . 8
= 16 + 24
= 30 (resposta)
(a + b)³ = (a + b).(a + b).(a + b)
= (a + b)². (a + b)
= ( a² + 2ab + b²) . (a + b)
= a³ + 2a²b + ab² + a²b + 2ab² + b³
= a³ + b³ + 3.a²b + 3.ab²
= a³ + b³ + 3.(a²b + ab²) (substituindo)
= 16 + 3 . 8
= 16 + 24
= 30 (resposta)
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás